2022
DOI: 10.5414/alx02331e
|View full text |Cite
|
Sign up to set email alerts
|

Guideline on allergen immunotherapy in IgE-mediated allergic diseases

Abstract: Not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 359 publications
0
57
0
5
Order By: Relevance
“…The expected duration of AIT is 3 years even though a longer treatment duration is possible and many manufacturers' recommendations state that application should be 3–5 years. 6 In our real‐world study, overall persistence across all allergen categories and AIT groups was low and decreased gradually over the entire analysis timespan, particularly after the first year. There are various possible reasons for treatment cessation, including strong side effects, lack of efficacy, or spontaneous contraindication (e.g.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The expected duration of AIT is 3 years even though a longer treatment duration is possible and many manufacturers' recommendations state that application should be 3–5 years. 6 In our real‐world study, overall persistence across all allergen categories and AIT groups was low and decreased gradually over the entire analysis timespan, particularly after the first year. There are various possible reasons for treatment cessation, including strong side effects, lack of efficacy, or spontaneous contraindication (e.g.…”
Section: Discussionmentioning
confidence: 70%
“…It is known that SLIT application leads to a higher rate of milder but discomforting side effects such as oromucosal pruritus or gastric discomfort, especially during the first weeks of therapy. 5 , 6 , 23 , 24 This might explain the poorer persistence of SLIT patients. Furthermore, the results have shown that a drop of adherence is seen earlier in the SLIT group than in the SCIT groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations